Threats and climate risks into vulnerable populations. The role of education in the community resilience - González-Gaudiano, Edgar Javier; Maldonado-González, Ana Lucía (Teoría de la Educación. Revista Interuniversitaria, 2017)
Nowadays, challenges in the contemporary world lead to the education to propose its current themes. Environmental education is not an exception. The magnitude and complexity of global environmental problems such as the climate change, the ocean acidification and the loss of the biodiversity have generated issues that had attracted pedagogical attention for decades. This article presents the early results of a study aimed at assessing the perception of risk and vulnerability of communities that frequently are affected by extreme hydrometeorological phenomena. These findings could be a starting point for the design of educational programs aimed at strengthening community resilience. We start from the assumption based on socio-cognitive factors that determine the dispositions in order to the populations can act under similar circumstances, we can find key elements that allow us to infer their reactions to difficult situations. This considering their previous experience and their singularities in the adaptation to climate change, in the social learning in extreme situations and in the identification of their strengths and weaknesses. Los inéditos desafíos del mundo contemporáneo obligan a la educación a replantear sus temas convencionales. La educación ambiental no es la excepción. La magnitud y complejidad de problemas ambientales globales como el cambio climático, la acidificación oceánica y la pérdida de la biodiversidad planetaria han relegado los asuntos que habían ocupado la atención pedagógica en este campo durante décadas. En este artículo se presentan los resultados iniciales de un estudio dirigido a valorar la percepción del riesgo y de vulnerabilidad de comunidades que de manera recurrente son afectadas por fenómenos hidrometeorológicos extremos. Los hallazgos han de fungir como punto de partida para el diseño de programas educativos orientados a fortalecer la resiliencia comunitaria. Partimos del supuesto de que, al basarnos en factores sociocognitivos que determinan las disposiciones a actuar por parte de poblaciones bajo presiones similares, podemos encontrar claves que nos permitan interpretar sus reacciones frente a situaciones difíciles. Esto considerando su experiencia previa y sus singularidades en la adaptación al cambio climático, en el aprendizaje social en momentos extremos y en la identificación de sus fortalezas y debilidades. Aujourd’hui, les défis au monde contemporain incitent à l’éducation à renouveler leurs actuels sujets d’etude. Évidemment, l’éducation environnementale ne fait pas l’exception. Tant la magnitude autant que la complexité des problèmes environnementaux mondiaux tels que le changement climatique, l’acidification des océans et la perte de la biodiversité mondiale ont oubli les questions qui avaient attiré l’attention pédagogique pendant des décennies. Dans cet article, on aborde les premiers résultats d’une étude visant à évaluer la perception du risque et de la vulnérabilité des communautés qui se sont vues affectées par des phénomènes météorologiques extrêmes. Les résultats donneront des pistes et des bases estratégiques afin de concevoir des programmes éducatifs visant à renforcer la résilience des communautés. D’après nous, à partir des facteurs socio-cognitifs qui déterminent les dispositions à agir de la part des populations sous des conditions similaires, nous pouvons trouver des indices qui nous permettent d’interpréter leurs réactions à des situations défavorables, compte tenu de leur expérience et de leurs singularités dans l’adaptation au changement climatique, dans l’apprentissage social sur des situations extrêmes et dans l’identification de leurs forces et de leurs faiblesses.